Comparison of adaptive pacing therapy, cognitive behaviour therapy, graded exercise therapy, and specialist medical care for chronic fatigue syndrome (PACE): a randomised trial - White, PD (Lancet Publishing Group, 2011)
BACKGROUND: Trial findings show cognitive behaviour therapy (CBT) and graded exercise therapy (GET) can be effective treatments for chronic fatigue syndrome, but patients' organisations have reported that these treatments can be harmful and favour pacing and specialist health care. We aimed to assess effectiveness and safety of all four treatments. METHODS: In our parallel-group randomised trial, patients meeting Oxford criteria for chronic fatigue syndrome were recruited from six secondary-care clinics in the UK and randomly allocated by computer-generated sequence to receive specialist medical care (SMC) alone or with adaptive pacing therapy (APT), CBT, or GET. Primary outcomes were fatigue (measured by Chalder fatigue questionnaire score) and physical function (measured by short form-36 subscale score) up to 52 weeks after randomisation, and safety was assessed primarily by recording all serious adverse events, including serious adverse reactions to trial treatments. Primary outcomes were rated by participants, who were necessarily unmasked to treatment assignment; the statistician was masked to treatment assignment for the analysis of primary outcomes. We used longitudinal regression models to compare SMC alone with other treatments, APT with CBT, and APT with GET. The final analysis included all participants for whom we had data for primary outcomes. This trial is registered at http://isrctn.org, number ISRCTN54285094. FINDINGS: We recruited 641 eligible patients, of whom 160 were assigned to the APT group, 161 to the CBT group, 160 to the GET group, and 160 to the SMC-alone group. Compared with SMC alone, mean fatigue scores at 52 weeks were 3·4 (95% CI 1·8 to 5·0) points lower for CBT (p=0·0001) and 3·2 (1·7 to 4·8) points lower for GET (p=0·0003), but did not differ for APT (0·7 [−0·9 to 2·3] points lower; p=0·38). Compared with SMC alone, mean physical function scores were 7·1 (2·0 to 12·1) points higher for CBT (p=0·0068) and 9·4 (4·4 to 14·4) points higher for GET (p=0·0005), but did not differ for APT (3·4 [−1·6 to 8·4] points lower; p=0·18). Compared with APT, CBT and GET were associated with less fatigue (CBT p=0·0027; GET p=0·0059) and better physical function (CBT p=0·0002; GET p<0·0001). Subgroup analysis of 427 participants meeting international criteria for chronic fatigue syndrome and 329 participants meeting London criteria for myalgic encephalomyelitis yielded equivalent results. Serious adverse reactions were recorded in two (1%) of 159 participants in the APT group, three (2%) of 161 in the CBT group, two (1%) of 160 in the GET group, and two (1%) of 160 in the SMC-alone group. INTERPRETATION: CBT and GET can safely be added to SMC to moderately improve outcomes for chronic fatigue syndrome, but APT is not an effective addition. FUNDING: UK Medical Research Council, Department of Health for England, Scottish Chief Scientist Office, Department for Work and Pensions.